Roles and Tasks of Social Workers in Chinese Disaster Management. (17th June 2022) - Sim, Timothy; He, Minying; Chen, Huiquan; Yang, Wanqiu
Abstract: Although social workers are often deeply involved in disaster management, their distinct roles and tasks in its various phases have not been adequately recognised. This may impede social work training and practice in disaster contexts and particularly in China, which regularly experiences disasters. In this study, we investigated the unique roles and tasks of Chinese social workers in disaster management. We conducted thirty-two in-depth interviews with stakeholders including front line social workers, academics, government officials, other professionals and survivors, and a content analysis. We identified the three main roles of social workers as conduits, mediators and providers of psychosocial support. We then assessed the complexity of social workers' roles and tasks in the Chinese context, and the potential for the strategic integration of social workers into a top-down disaster management system. Abstract : The study focuses on the distinct roles and tasks of Chinese social workers in disaster management. After interviewing thirty-two experienced stakeholders, three key social worker roles were identified: (1) As conduits between various disciplines, sectors and stakeholders. (2) As strategic mediators between the government and residents. (3) As providers of psychosocial support at different levels. These roles and the corresponding tasks are closely related to the Chinese disaster management system.